Unique Voice Owner (Dedicated To The Memory Of Botir Zokirov) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the favorite artist of our people, the People's Artist of Uzbekistan Botir Zakirov. Although a lot of information has been written about this artist, due to the bright mark he left on Uzbek art, it seems that there is little to write about. Because B.Zokirov founded the Uzbek pop art, along with his contribution to this performing direction, it was also discussed about his family, which played an important role in his reaching this level.